The whole chloroplast genomes of two Eutrema species (Brassicaceae). (2nd September 2016) - Hao, Guoqian; Bi, Hao; Li, Yuanshuo; He, Qi; Ma, Yazhen; Guo, Xinyi; Ma, Tao
Abstract: In this study, we determined the complete chloroplast genomes from two crucifer species of the Eutrema genus. The sizes of the two cp genomes were 153 948 bp ( E. yunnanense ) and 153 876 bp ( E. heterophyllum ). Both genomes have the typical quadripartite structure consisting of a large single copy region, a small single copy region and two inverted repeats. Gene contents and their relative positions of the 132 individual genes (87 protein-coding genes, eight rRNA, and 37 tRNA genes) of either genome were identical to each other. Phylogenetic analysis supports the idea that the currently recognized Eutrema genus is monophyletic and that E. salsugineum and Schrenkiella parvula evolved salt tolerance independently.